Implementation of English Learning at Batu Ampar 02 East Jakarta Elementary School with Innovative Artificial Intelligence Technology - Ithriyah, Siti; Fitri Meilana, Septi (ISLAMIKA, 2025)
The use of AI technology in education has grown rapidly in recent years. English language education in Indonesia, especially at the primary school level, has become one of the important focuses in the national curriculum. The main goal of this study is to evaluate the effectiveness of using AI in English language learning. This study uses a qualitative approach with a case study design to explore the implementation of artificial intelligence (AI) technology in English learning at Batu Ampar 02 Elementary School, East Jakarta. The results of this study show that the implementation of artificial intelligence (AI) technology in English learning has a very positive impact on students' English language skills. Data obtained through interviews, observations, and document analysis show that AI technology has succeeded in increasing students' confidence in speaking English. More than 70% of students who were initially reluctant to speak now feel more confident, and 75% of students report feeling more comfortable speaking in front of their peers after using an AI-based app that allows speaking practice with instant feedback. This proves that AI technology can overcome the social and psychological barriers that students often face in learning English, especially in speaking skills. In addition, students' motivation to learn has also increased significantly. About 85% of students revealed that they felt more motivated to learn English after using an AI application that integrates educational games and challenge-based exercises.